Identificação e alternativas para destinação da fração de resíduos sólidos orgânicos no zoológico: um estudo no zoológico de Cascavel - PR - Girelli, Patricia Lucia Linzmeyer (2019)
For thousands of years, the Zoos exist changing its main purpose with time. At present, the exhibition of animals is not the main role of the Zoo, which is now mainly characterized by scientific research, conservation biology, and environmental education. The Zoos must be registered on the federal record as presenting potentially pollutant activities with possible use environmental resources – CTF/APP, in agreement with the Normative Instruction of IBAMA nº 07, from April 30th, 2015. Furthermore, the Zoo activities must also abide several laws related to Zoos, e.g. law nº 7173 from December 14th, 1983, therefore, demanding an efficient water management. This work aims to identify the organic solid waste fraction in the Zoo from Cascavel (PR, Brazil), and propose a sustainable alternative for its disposal. In this regard, it was carried out an extensive research on documents, bibliography, and periodic. Through an observation in-loco, it was analyzed the Zoo structure and the employees routine regarding to animal feed, maintenance of the Zoo, and separation of the collected wastes. It was identified the organic solid waste sources, and this material was characterized, graded, and finally different alternatives for the waste disposal were suggested. This research provided fundamental information for the management of the organic solid waste fraction of the Zoo, and its variation with time. The sustainable alternative and analysis of the organic solid waste disposal proposed in this work assists the Zoo to abide the law, which determines the correct disposal of the solid organic wastes (law 12.305/2010, Art. 36).